Comparison of the Efficacy of Anatomic and Non-anatomic Hepatectomy for Hepatic Alveolar Echinococcosis: Clinical Experience of 240 Cases in a Single Center - A, Jide; Zhang, Jingni; Chai, Jinping; Zhao, Shunyun; Wang, Hao; A, Xiangren; Yang, Jinyu (Frontiers in Public Health, 2022)
Introduction: Hepatic alveolar echinococcosis (HAE) is a zoonotic parasitic disease. There are more than 16,000 new cases each year, approximately 60 million people are threatened, and the annual direct economic loss is RMB 3 billion. The prevalence of alveolar echinococcosis (AE) in some areas of the Qinghai–Tibet Plateau is as high as 6.0%. Radical resection for advanced HAE can significantly prolong the survival time of patients. Therefore, by comparing various clinical evaluation indices between anatomic and non-anatomic hepatectomy, this study explores the short-term and long-term efficacy of the two surgical methods for HAE. Methods: The clinical data of patients with HAE who underwent radical hepatectomy at Qinghai Provincial People’s Hospital from January 2015 to January 2021 were retrospectively analyzed. The patients were divided into two groups by surgical method, that is, the non-anatomic hepatectomy group and the anatomic hepatectomy group. We compared the two groups on their basic preoperative data, such as age, sex, hydatid size, and liver function indices; the main intraoperative evaluation indices, such as operation time, intraoperative porta hepatis occlusion time, intraoperative blood loss, and blood transfusion; and postoperative recovery evaluation indices, such as postoperative liver function, incidence of surgical complications, and AE recurrence. Results: A total of 240 patients were enrolled in this clinical study, including 123 in the anatomic hepatectomy group and 117 in the non-anatomic hepatectomy group. There were no significant differences (P ˃ 0.05) in the preoperative data of the two groups. There were statistically significant differences in intraoperative blood loss (P < 0.001), blood transfusion (P < 0.001), and porta hepatis occlusion time (P < 0.001). There were statistically significant differences in postoperative liver function (aspartate aminotransferase: P < 0.001; alanine aminotransferase: P < 0.001), surgical complications (P < 0.001), and AE recurrence rate (P = 0.003). The median survival time of patients in the anatomic hepatectomy group was 66 months, compared to 65 months in the non-anatomic hepatectomy group (= 4.662, P = 0.031). Conclusion: Anatomic hepatectomy not only is safe and reliable for HAE but also has better short-term and long-term efficacy than non-anatomic hepatectomy.